If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(y-3)=10
We move all terms to the left:
-2(y-3)-(10)=0
We multiply parentheses
-2y+6-10=0
We add all the numbers together, and all the variables
-2y-4=0
We move all terms containing y to the left, all other terms to the right
-2y=4
y=4/-2
y=-2
| b=-75 | | (3x+14)=(7x-4)=180 | | (2b-1)=(4b-3) | | 5x-10=7x+4=180 | | ½(y-8)=3.5y+8 | | 23-8x=2x+9 | | -10+x=24 | | Y=24+12c | | 4+2x-7=180 | | 9=-v-6 | | 7(2x-3)=8x+39 | | 3x+3=-2x-17−2x−17 | | 7x+8+10x+2=180 | | 3a÷3=6 | | -3x-4-2x+9=-1 | | -27-3.53f=-41 | | x-18=0.5*(x+7) | | $150+$40.50x=$120+$46.75x | | 3b+8-4=22 | | x-18=0.5*x+7 | | 19=p23 | | -5-3(6x-8)=x+19 | | 15x=2.4 | | -34=2m | | 6x-20=73x+10 | | 866520=x335 | | (3+11i)/(-1-2i)=0 | | 6.25=w/ | | 2(3x-4)=-6x+16 | | 1=y/7+9 | | x+51-x+341=180 | | 52=4w+8 |